“Wawasan Brunei 2035”: Analyzing The Vision of Brunei Darussalam on National Security and State Welfare - Halim Widyawardhana; Yusuf Ali; Triyoga Budi Prasetyo (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2018)
Abstract – Security plays an important role in creating peaceful condition in a country. By having a secure nation, the people of the nation may have freedom in the aspects of economy, politics, social interaction, religion, and other aspects. Unfortunately, threats may come from anywhere and various in forms. Terrorism and Cyber Attacks become two of the greatest concerns in term of security world widely and this may be troublesome to Brunei. This paper aims to analyze wawasan Brunei 2035 on national security and state walfare. This paper used qualitative method and the data is gained from documents, archives, journal and so on. The research result that in order to prevent and counter the threats, Brunei Darussalam formulates the Wawasan Brunei 2035 or the Brunei’s Vision 2035 as a means to create security and increasing the welfare of the state. In this paper, the author utilizes the synergy theory to analyze. Keywords: Wawasan Brunei 2035, Security, Welfare. Abstrak – Keamanan memainkan peranan penting dalam menciptakan perdamaian dan ketentraman di dalam sebuah negara. Dengan memiliki negara yang aman, masyarakat dari suatu negara akan memiliki kebebasan dalam aspek ekonomi, politik, interaksi sosial, agama, dan aspek lainnya. Sayangnya, ancaman dapat muncul dari manapun dan dalam bentuk yang beragam. Terorisme dan serangan siber menjadi perhatian dalam keamanan di dunia dan dapat menjadi masalah untuk Brunei. Penelitian ini bertujuan untuk menganalisa wawasan Brunei 2035 dalam keamanan dan kesejahteraan negaranya. Penelitian ini utamanya menggunakan teori keamanan dalam menganalisis data yang ada. Peneitian ini menggunakan pendekatan kualitatif dan sumber datanya berasal dari dokumen, arsip maupun jurnal. Hasil penelitian menunjukan bahwa untuk mencegah dan mengatasi ancaman ini, Brunei Darussalam merumuskan Wawasan Brunei 2035 sebagai cara untuk menciptakan keamanan dan meningkatkan kesejahteraan negara.Kata kunci: Wawasan Brunei 2035, Keamanan, Kesejahteraan